2021
DOI: 10.1039/d1fo00031d
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin regulates skeletal muscle fiber type switching via adiponectin signaling

Abstract: This study aimed to investigate the role and underlying molecular mechanism of quercetin in regulating skeletal muscle fiber type transition. We found that dietary quercetin supplementation in mice significantly increased...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
2
28
0
3
Order By: Relevance
“…Interestingly, in this study, the addition of maca regulated skeletal muscle fiber type, especially MyHC-fast ( Figure 2 A). Previous studies showed that quercetin significantly increased the protein expression of MyHC-slow and significantly decreased MyHC-fast protein expression [ 26 ]. Since quercetin is also found in maca [ 27 ], we considered that maca may also have affected MyHC-slow, but no significant difference was detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study, the addition of maca regulated skeletal muscle fiber type, especially MyHC-fast ( Figure 2 A). Previous studies showed that quercetin significantly increased the protein expression of MyHC-slow and significantly decreased MyHC-fast protein expression [ 26 ]. Since quercetin is also found in maca [ 27 ], we considered that maca may also have affected MyHC-slow, but no significant difference was detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding argues that innervation may play a dominant role in specifying fiber type by defining myofibrillar calcium oscillation and downstream signaling events ( Olson and Williams, 2000 ) required to match the metabolism of the cell with the contractile properties. On the other hand, shifting metabolism from oxidative to glycolytic phenotype, or vice versa, often leads to fiber type switching in the opposite direction ( Wen et al, 2020 ; Xu et al, 2020a , b ; Chen et al, 2021 ). For example, feeding mice with clenbuterol induces the de novo synthesis of IIX and IIB fibers in mouse soleus muscle, whose component are exclusively type I and IIA fiber ( Shi et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies provide more evidence to support the notion that metabolites can drive muscle fiber switching through AMPK-PGC1α axis. For examples, quercetin, found in many fruits, vegetables and grains, can induce muscle fiber switching to a more oxidative phenotype through adiponectin-AMPK-PGC-1α pathway ( Chen et al, 2021 ). Dietary supplementation of arginine to mouse induces fast- to slow-twitch fiber type transition, accompanied by an upregulation of Sirt1/AMPK pathway ( Chen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Slow muscle fiber contains more mitochondria, has oxidative metabolism at a high level, and exhibits strong sustained contractile capacity. Studies indicated that skeletal muscle fiber type switching from fast to slow fiber is important for the improvement of fatigue, alleviation of insulin resistance, and maintenance of body energy homeostasis. ,, Recently, increasing studies showed that natural products could induce skeletal muscle remodeling and increase the proportion of slow muscle fiber. For instance, quercetin regulates skeletal muscle fiber type switching from glycolytic type II to oxidative type I; procyanidin B2 changes the composition proportion of myofiber types and increases slow muscle fiber gene expression; and lycopene promotes mitochondrial respiration, reduces glycolysis metabolism, and activates slow muscle fiber expression . In the present study, we found that naringin treatment could significantly increase oxidative enzymatic activity (SDH), up-regulate the expression of slow fiber-related genes TNNT1, PGC-1α, myoglobin, and MyHC I, and activate MyHC I protein expression, as well as decrease α-GPDH activity (α-GPDH is a hallmark of glycolytic metabolism, which is positively correlated with the proportion of IIb myofiber), down-regulate the expression of fast fiber-related genes TNNT3 and MyHC IIb expression, and reduce MyHC IIb protein expression.…”
Section: Discussionmentioning
confidence: 99%